2018
DOI: 10.1111/jpm.12464
|View full text |Cite
|
Sign up to set email alerts
|

The health professional experience of using antipsychotic medication for dementia in care homes: A study using grounded theory and focussing on inappropriate prescribing

Abstract: Positive perceptions based on past experiences with antipsychotics should be challenged through future interventions that tackle inappropriate prescribing, for example using behaviour change techniques to better highlight adverse consequences of prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…With regard to LPN staffing our findings are in contrast to prior research which showed that when there was more LPN staffing there was greater use of psychotropic medications (Lucas et al, 2014). We anticipate that these differences are due to beliefs of the staff member rather than his or her degree or qualifications (Almutairi et al, 2018; Kerns et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to LPN staffing our findings are in contrast to prior research which showed that when there was more LPN staffing there was greater use of psychotropic medications (Lucas et al, 2014). We anticipate that these differences are due to beliefs of the staff member rather than his or her degree or qualifications (Almutairi et al, 2018; Kerns et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the proposed models in this study explained very little of the variance in psychotropic medication use or in the use of opiates. Additional factors that should be considered in future research are beliefs of the staff, access to behavioral health providers, the use of person centered behavioral interventions, activities provided, length of stay of the resident, and timing of medication initiation (Almutairi et al, 2018; Atramont et al, 2018; Helvik et al, 2017; Janus et al, 2018; Kerns et al, 2018; MacLagan et al, 2017; Zhang, Letuchy, & Carnahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite publications covering the topic generally [ 18 , 19 ], on closer scrutiny, no guidance detailed how to undertake a GT synthesis of data using existing publications as the data source. The authors therefore shaped their own methodology, drawing heavily on the work of Atkins et al (2008) [ 20 ] for the data extraction elements and using previous GT expertise for the detailed data analysis [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…10 Administering an APM is often viewed as an easier solution to control behaviors when staff are faced with time restraints, minimal knowledge on behavioral approaches, and the perception that APMs are efficacious and low-risk. 1113…”
Section: Introductionmentioning
confidence: 99%